Does India Have an International Strategy? - Lavakare, Prabhakar (International Higher Education, 2013)
There is a movement across the world to internationalize higher education so that it meets the needs of students to be more global in their approach to higher education. Various strategies are being worked out by different countries to understand the meaning of internationalization and how it can be imparted in national educational institutions. Unfortunately, in India, the higher education system is not being subjected to this process of internationalization. India's latest five year plan (2012-17) for national development has a brief mention about internationalization, but no concrete measures to bring about this change in the higher education system have been formulated so far)